A Systematic Review of Treatment Options and Clinical Outcomes in Pemphigoid Gestationis - Genovese, Giovanni; Derlino, Federica; Cerri, Amilcare; Moltrasio, Chiara; Muratori, Simona; Berti, Emilio; Marzano, Angelo Valerio (Frontiers in Medicine, 2020)
Background Treatment regimens for pemphigoid gestationis (PG) are non-standardized, with most evidence derived from individual case reports or small series. Objectives To systematically review current literature on treatments and clinical outcomes of PG and to establish recommendations on its therapeutic management. Methods An a priori protocol was designed based on PRISMA guidelines. PubMed, Scopus and Web of Science databases were searched for English-language articles detailing PG treatments and clinical outcomes, published between 1970 and March 2020. Results In total, 109 articles including 140 PG patients were analyzed. No randomized controlled trials or robust observational studies detailing PG treatment were found. Systemic corticosteroids ± topical corticosteroids and/or antihistamines were the most frequently prescribed treatment modality (n=74/137; 54%). Complete remission was achieved by 114/136 (83.8%) patients. Sixty-four patients (45.7%) were given more than one treatment modality due to side effects or ineffectiveness. Leaving aside topical corticosteroids as monotherapy ± antihistamines in patients with mild disease, systemic corticosteroids ± topical corticosteroids and/or antihistamines led to complete remission in the highest proportion of patients (83%), while steroid-sparing treatments ± topical corticosteroids and/or antihistamines were associated with the lowest proportion of flares (55.5%). Limitations The review has been drafted based on a limited number of single case reports and small case series. Underreporting/underdiagnosis of patients with mild-to-moderate PG, partial/absent follow-up, absence of precise description of neonatal outcomes and lack of validated objective scores for measuring disease severity are other limitations of our study. Our systematic review was affected by publication bias. Conclusion Systemic corticosteroids are the most frequently used treatment for PG. Whilst most patients achieve complete remission, many of them have refractory/persistent disease requiring multiple lines of therapy. Therefore, we provided an algorithm for PG treatment integrating the results of this systematic review with current knowledge available for bullous pemphigoid. High-quality studies will further help assess the effectiveness of different treatment options for PG.